2017
DOI: 10.1039/c7ta00590c
|View full text |Cite
|
Sign up to set email alerts
|

A nitrogen-rich fluorescent conjugated microporous polymer with triazine and triphenylamine units for high iodine capture and nitro aromatic compound detection

Abstract: A new kind of nitrogen-rich fluorescent conjugated microporous polymer TTPB was synthesized via a Friedel–Crafts reaction of 2,4,6-trichloro-1,3,5-triazine and N,N,N′,N′-tetraphenylbenzidine catalyzed by methanesulfonic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(123 citation statements)
references
References 31 publications
4
119
0
Order By: Relevance
“…As shown in Figure (A), all adsorbents have similar adsorption rate for iodine uptake within initial 1 h, while the saturated adsorption capacity at eventual adsorption equilibrium state are totally varied. For example, NH 2 ‐HMONs and NH 2 ‐HCPS both perform higher iodine uptake than HMONs and HCPS, respectively, which indicates that the amino groups can make great contributions to the enhanced iodine adsorption capacity due to the interaction between nitrogen atom and iodine . The similar enhanced tendency can also be observed for NH 2 ‐HMONs and HOMNs compared with NH 2 ‐HCPS and HCPS, respectively, which further demonstrate the importance of hollow spherical structure for the enhanced iodine capture.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…As shown in Figure (A), all adsorbents have similar adsorption rate for iodine uptake within initial 1 h, while the saturated adsorption capacity at eventual adsorption equilibrium state are totally varied. For example, NH 2 ‐HMONs and NH 2 ‐HCPS both perform higher iodine uptake than HMONs and HCPS, respectively, which indicates that the amino groups can make great contributions to the enhanced iodine adsorption capacity due to the interaction between nitrogen atom and iodine . The similar enhanced tendency can also be observed for NH 2 ‐HMONs and HOMNs compared with NH 2 ‐HCPS and HCPS, respectively, which further demonstrate the importance of hollow spherical structure for the enhanced iodine capture.…”
Section: Resultsmentioning
confidence: 65%
“…For example, NH 2 -HMONs and NH 2 -HCPS both perform higher iodine uptake than HMONs and HCPS, respectively, which indicates that the amino groups can make great contributions to the enhanced iodine adsorption capacity due to the interaction between nitrogen atom and iodine. [32][33][34][35] The similar enhanced tendency can also be observed for NH 2 -HMONs and HOMNs compared with NH 2 -HCPS and HCPS, respectively, which further demonstrate the importance of hollow spherical structure for the enhanced iodine capture. However, TEM image (Supporting Information Fig.…”
Section: Uptakementioning
confidence: 56%
“…Considering these PANs have the same nitrogen atom and triazine ring numbers in the structural units, we proposed the pore size and volume and the content of polar pyrrolyl groups and BDP units might play the most important roles in the iodine adsorption capacities . The lone electron pair of nitrogen might have strong affinity for the iodine by formation of a charge transfer complex . The PAN3, with moderate pore size and high density of nitrogen, not only captured the iodine vapor by the conjugated moiety on the pore surface, but also adsorbed iodine molecules by chemical iodination and charge‐transfer interaction with polyiodine anions, thus showing the highest capacity among the five PANs.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, POPs as absorbents for capturing volatile iodine have gained attention due to environmental issues . Radiated iodine from medical waste and nuclear waste could cause serious health problems .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there was attracted considerable attention in the research of novel porous organic polymers (POPs) that have demonstrated great application prospect in iodine capture and fluorescence sensing to iodine and nitroaromatic compounds (NACs) . POPs have developed into a variety of types, including covalent organic frameworks (COFs), polymers of intrinsic microporosity (PIMs), hyper‐cross‐linked polymers (HCPs), covalent triazine‐based frameworks (CTFs), and conjugated microporous polymers (CMPs) …”
Section: Introductionmentioning
confidence: 99%